2014
DOI: 10.7314/apjcp.2014.15.21.9117
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception and Attitude Towards Human Papillomavirus among Pre-university Students in Malaysia

Abstract: Background: To evaluate the knowledge, perception and attitudes towards human papilloma virus (HPV) among pre-university students in Malaysia. Study design : In this cross sectional study, between November 2013 to March 2014, in a public university, a convenient sampling method was used. A total of 716 respondents were recruited and interviewed with a set of standard questionnaires for assessment of knowledge, perception and attitudes towards HPV and predictor variables associated with level of knowledge. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
6
18
0
Order By: Relevance
“…There was moderate knowledge mean score seen in this study which was similarly noted among pre-university students [1 ]. Most of the students (76.4%) knew the purpose of HPV vaccination which is similar to the other two studies conducted in Malaysia with 67.9% and 73.2%, respectively [1,10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There was moderate knowledge mean score seen in this study which was similarly noted among pre-university students [1 ]. Most of the students (76.4%) knew the purpose of HPV vaccination which is similar to the other two studies conducted in Malaysia with 67.9% and 73.2%, respectively [1,10].…”
Section: Discussionsupporting
confidence: 84%
“…Human papillomavirus (HPV) is the most common viral infection of the reproductive system, and it is one of the most common sexually transmitted diseases [1,2]. Approximately 99% of the cervical cancer cases are contributed by HPV infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Their awareness and understanding of basic HPV and HPV vaccine knowledge is a very important part of the preventive strategies. In general, published reports from many countries shown that there is a significant deficiency in HPV and HPV vaccine knowledge among adolescents . It may be due to lack of effective education or counseling by the family, society, or health‐care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In general, published reports from many countries shown that there is a significant deficiency in HPV and HPV vaccine knowledge among adolescents. [5][6][7][8] It may be due to lack of effective education or counseling by the family, society, or health-care professionals. In addition to the poor knowledge, some studies also reported that adolescents have low perception of risk, that is, they perceived themselves as not being vulnerable to HPV infection or other sexually transmitted infections (STI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation